Nutrient Content of Lettuce Plants in a Hydroponic System with the Addition of Acid Solution: Kandungan Hara Tanaman Selada pada Sistem Hidroponik dengan Penambahan Larutan Asam - Zulfarosda, Ratna; Purnamasari, Retno Tri; Fibriani, Vita (Journal of Applied Plant Technology, 2023)
Hydroponics is a plant cultivation technique that uses water as a growing medium. The acidity level (pH) of water is an important factor in the success of hydroponic plant cultivation. High water acidity (pH>8) can be controlled by adding acid solution to a pH level of 5.8-7.0. This research was conducted to examine the nutrient content of lettuce. The research used a Randomized Block Design with 9 treatments (3 types of water and 3 types of acid solution). The types of water used include Kebonsari well water, Bugul Kidul well water and Pasuruan city PDAM water. The acid solutions used include nitric acid, phosphoric acid and sulfuric acid. The results of the research show that adding acid solutions to all types of water produces different plant nutrient contents. The addition of nitric acid and phosphoric acid solutions respectively had a significant effect on the N and P nutrient content of lettuce plants. The addition of phosphate solution can be recommended as a pH lowering solution in hydroponic cultivation.